Towards the development of a novel taxonomy of knowledge management systems from a learning perspective: an integrated approach to learning and knowledge infrastructures - Lytras, Miltiadis D; Pouloudi, Athanasia (Journal of knowledge management, 2006)
Purpose - The paper aims to discuss the critical issue of learning and knowledge convergence in knowledge-intensive organizations, and to provide practical guidelines for effective strategies.Design methodology approach - The paper brings together previous research in knowledge management and provides a critique for the lack of integration of previous studies with learning, a key process for efficient knowledge management. Stemming from this critique, an integrative framework for knowledge management support from a learning perspective is proposed.Findings - The major contribution is the framework for knowledge management support from a learning perspective, which can guide strategies of effective knowledge and learning management. This framework initiates an interesting discussion of technological issues that can enhance current knowledge management practices.Research limitations implications - The taxonomy of knowledge management systems provides the basis for an extensive specification of knowledge management strategies. Further research could focus on an instrumental approach to the integrative framework suggested in this paper, to illustrate how it can be used to enhance the integration of learning processes and products in the knowledge management process.Practical implications - The paper is a very useful source of information and impartial advice for strategists, knowledge management officers and people interested in implementing learning and knowledge management in a knowledge-intensive organization.Originality value - This paper presents a novel taxonomy of knowledge management systems from a learning perspective. Unlike previous literature on knowledge management, this paper makes an explicit claim for integrating knowledge management and learning activities and illustrates how the two can be jointly supported by various knowledge management systems.